Antigen-Experienced CD4lo T Cells Are Linked to Deficient Contraction of the Immune Response in Autoimmune Diabetes. (24th August 2010) - Linkes, Sean; Fry, Christopher; Quinn, Anthony
Abstract : Following proper activation, naïve "CD4lo" T cells differentiate into effector T cells with enhanced expression of CD4 -"CD4hi" effectors. Autoimmune diabetes-prone NOD mice display a unique set of antigen-experienced "CD4lo" T cells that persist after primary stimulation. Here, we report that a population of such cells remained after secondary and tertiary TCR stimulation and produced cytokines upon antigenic challenge. However, when NOD blasts were induced in the presence of rIL-15, the number of antigen-experienced "CD4lo" T cells was significantly reduced. Clonal contraction, mediated in part by CD95-dependent activation-induced cell death (AICD), normally regulates the accumulation of "CD4hi" effectors. Interestingly, CD95 expression was dramatically reduced on the AICD-resistant NOD "CD4lo" T cells. Thus, while autoimmune disease has often been attributed to the engagement of robust autoimmunity, we suggest that the inability to effectively contract the immune response distinguishes benign autoimmunity from progressive autoimmune diseases that are characterized by chronic T cell-mediated inflammation.